2015
DOI: 10.1080/13607863.2015.1031635
|View full text |Cite
|
Sign up to set email alerts
|

Feasibility of a pocket-PC based cognitive control intervention in dementia spousal caregivers

Abstract: Objectives Spousal caregivers of patients with dementia are in need of interventions to bolster their quality of life. Computer-based, self-administered cognitive training is an innovative approach to targeting spousal caregiver distress and coping. We tested the feasibility of administering one such intervention with minimal clinician intervention. Methods Twenty-seven elderly adults (> 64 years old), who each were the primary caregiver for a spouse with dementia, were recruited through the Memory Disorders… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
44
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(45 citation statements)
references
References 48 publications
1
44
0
Order By: Relevance
“… 80% Mohide [ 65 ], 1990 Caregivers Social intervention, help the caregivers enhance caregiving competence and achieve a sense of control in their roles as caregivers 70% Eloniemi-Sulkava [ 54 ], 2009 Dyads Multi-component support program, include goal-oriented peer support group meetings, dementia education, 100% Martin-Carrasco [ 40 ], 2009 Caregivers Cognitive intervention, include behavioural problems handing strategies, tension and stress control, dementia education. 90.4% Wilz [ 48 ], 2016 Caregivers Cognitive intervention, Cognitive Behavioral Therapy 79.5% Callan [ 70 ], 2015 Caregivers Cognitive intervention, provide information about dementia, social support, coping skills training, affective self-management, and healthy sleep practices. 74% McCurry [ 61 ], 2015 Caregivers Cognitive intervention, include Problem-solving skills, Effective communication skills, negative thinking management, Coping strategies, education.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“… 80% Mohide [ 65 ], 1990 Caregivers Social intervention, help the caregivers enhance caregiving competence and achieve a sense of control in their roles as caregivers 70% Eloniemi-Sulkava [ 54 ], 2009 Dyads Multi-component support program, include goal-oriented peer support group meetings, dementia education, 100% Martin-Carrasco [ 40 ], 2009 Caregivers Cognitive intervention, include behavioural problems handing strategies, tension and stress control, dementia education. 90.4% Wilz [ 48 ], 2016 Caregivers Cognitive intervention, Cognitive Behavioral Therapy 79.5% Callan [ 70 ], 2015 Caregivers Cognitive intervention, provide information about dementia, social support, coping skills training, affective self-management, and healthy sleep practices. 74% McCurry [ 61 ], 2015 Caregivers Cognitive intervention, include Problem-solving skills, Effective communication skills, negative thinking management, Coping strategies, education.…”
Section: Resultsmentioning
confidence: 99%
“…Five low-quality papers reported data on participants’ completion rate for the interventions. Three studies showed moderate completion rate [ 34 , 69 , 70 ], while the other 2 reported low completion rate [ 67 , 68 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The summary of the relevant studies in this review suggests general positive outcomes for caregivers after using the digital mental health tool with a reported increase in coping skills or emotional regulation (8,10,22,27,31), a decrease in stress, and burden (7,22,31) as well as perceived improvements in motivation to care (23). There were no adverse effects of digital mental health tools reported, even in the population that had low familiarity with technology, which might be further argued as a limitation.…”
Section: Discussionmentioning
confidence: 99%
“…The amount of care provided mostly depends on the care recipientcaregiver relationship-e.g., spouse, parent, sibling, friend-and the living arrangements between the two. Caregiving role comes with diverse challenges, and many of those put caregivers at risk of mental health problems (7)(8)(9)(10) and even increased risk of mortality through the development of severe chronic conditions.…”
Section: Introductionmentioning
confidence: 99%